2014
DOI: 10.4236/ajps.2014.59143
|View full text |Cite
|
Sign up to set email alerts
|

Competition Indices of Intercropped Lupine (Local) and Small Cereals in Additive Series in West Gojam, North Western Ethiopia

Abstract: The experiment was conducted on intercropping of lupine (Lupinus albus L.) with wheat (Triticum aestivum), barley (Hordeum vulgar) and finger millet (Eleusine coracana) in 2009 at Adet Agricultural research station, in Western Gojam. The treatments were sole wheat at a seed rate of 175 kg/ha, sole barley at a seed rate of 125 kg/ha, sole finger millet at a seed rate of 30 kg/ha, sole lupine at a seed rate of 90 kg/ha, and an additive series of 25, 50 and 75% of the sole lupine seed rate combined with the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
4
24
1
Order By: Relevance
“…This probably due to early potato dominance did appear to suppress maize growth. This corroborates with Trydeman et al [31] and Bantie et al [6] who stated that barley (early harvested) was dominant over lupine (long duration to mature). Income equivalent ratio (IER): Income equivalent ratio for maize, potato and total were significantly (P<0.01) influenced by intercropping arraignments (Table 5).…”
Section: Ler Total Atersupporting
confidence: 92%
See 3 more Smart Citations
“…This probably due to early potato dominance did appear to suppress maize growth. This corroborates with Trydeman et al [31] and Bantie et al [6] who stated that barley (early harvested) was dominant over lupine (long duration to mature). Income equivalent ratio (IER): Income equivalent ratio for maize, potato and total were significantly (P<0.01) influenced by intercropping arraignments (Table 5).…”
Section: Ler Total Atersupporting
confidence: 92%
“…The result was in corroborates with Dhima et al [29], who reported that Vetch-barely intercropping in different seeding ratios gave negative EMAI as compared to sole cropping. Similarly, EMAI values in all lupine-barley combinations were found highly negative as compared to all pure stands due to very low LER caused by sever reduction in lupine yield [6]. Maximum negative value in the latter intercropping arraignments implying unsuitability arrangement showed an economic disadvantage.…”
Section: Ler Total Atermentioning
confidence: 84%
See 2 more Smart Citations
“…Most studies in Ethiopia have focused on cereal and legume intercropping and identified suitable genotype combinations, plantings dates, and population densities of various species while, little attention was given to other intercropping systems (Bantie et al 2014). Several authors have reported the superiority of maize/potato intercropping to sole (Amin et al 1996;Sharaiha Battikhi 2002;Tesfay et al 2006;Yayeh 2015).…”
mentioning
confidence: 99%